Investigation of soyasapogenols from soybean seed germs as Anti-apoptotic agents in colon cancer using an In silico approach - Vu, Trong Luong; Nguyen, Thi Ngoc Lan; Tu, Quang Tan; Nguyen, Duc Hung; Chu, Hoang Mau (Vietnam Journal of Biotechnology, 2026)
Colorectal cancer is one of the most common malignancies worldwide, with 1.9 million new cases and 903,859 deaths recorded in 2022. Current treatments remain constrained by limited efficacy and safety concerns, emphasizing the need for new therapeutic options. Soybean [Glycine max (L.) Merr.] seed germs are rich in triterpenoids and represent a promising source of anticancer compounds. Preliminary phytochemical analysis confirmed the presence of alkaloids, flavonoids, terpenoids, cardiac glycosides, coumarins, saponins, and tannins, while steroids were absent, reflecting the metabolic diversity of this material. This study investigated the anticancer activity of soyasapogenol A and B, triterpenoids derived from soybean seed germs, by inhibiting the anti-apoptotic protein Bcl-2. In silico docking analysis revealed that soyasapogenol B exhibited a higher binding affinity and more stable interaction with the Bcl-2 protein (PDB: 6GL8) compared to soyasapogenol A and the reference drug paclitaxel. Molecular dynamics simulations over 100 nanoseconds supported the persistence of these interactions. ADMET profiling using pkCSM predicted that soyasapogenol B exhibits favorable pharmacokinetic properties, including high intestinal absorption, moderate distribution, and the absence of significant toxicities. Collectively, these findings identify soyasapogenol B as a potential Bcl-2 inhibitor with therapeutic relevance to colorectal cancer. The results provide a basis for further experimental validation and the development of soybean seed germs-derived compounds as novel anticancer agents.